2012
DOI: 10.1038/aps.2012.62
|View full text |Cite
|
Sign up to set email alerts
|

Differential hepatoprotective mechanisms of rutin and quercetin in CCl4-intoxicated BALB/cN mice

Abstract: Aim: To investigate the mechanisms underlying the protective effects of quercetin-rutinoside (rutin) and its aglycone quercetin against CCl 4 -induced liver damage in mice. Methods: BALB/cN mice were intraperitoneally administered rutin (10, 50, and 150 mg/kg) or quercetin (50 mg/kg) once daily for 5 consecutive days, followed by the intraperitoneal injection of CCl 4 in olive oil (2 mL/kg, 10% v/v). The animals were sacrificed 24 h later. Blood was collected for measuring the activities of ALT and AST, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 47 publications
8
68
0
3
Order By: Relevance
“…Some previous studies have already demonstrated that quercetin can prevent CCl 4 -induced acute liver injury when given several days before CCl 4 intoxication (Janbaz et al, 2004;Domitrović et al, 2012;Cui et al, 2014). From the results of ALT/AST analysis and histological observations, our study demonstrates that quercetin can ameliorate CCl 4 -induced acute liver injury when it is given 30 min after CCl 4 intoxication.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Some previous studies have already demonstrated that quercetin can prevent CCl 4 -induced acute liver injury when given several days before CCl 4 intoxication (Janbaz et al, 2004;Domitrović et al, 2012;Cui et al, 2014). From the results of ALT/AST analysis and histological observations, our study demonstrates that quercetin can ameliorate CCl 4 -induced acute liver injury when it is given 30 min after CCl 4 intoxication.…”
Section: Discussionsupporting
confidence: 65%
“…Various reports show that quercetin has neuro-protection, anti-tumor, antiinflammation, anti-oxidant, and anti-diabetic effects (Chirumbolo, 2010;Kelly, 2011;Dajas, 2012). Furthermore, some reports demonstrate that quercetin can ameliorate various toxin-induced liver injuries, such as ethanol and acetaminophen (Vicente-Sánchez et al, 2008;Liu et al, 2010;Yousef et al, 2010;de David et al, 2011;Domitrović et al, 2012). However, the concrete-engaged signals in regulating the protection of quercetin against liver injuries are not very clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[50] The high amount of quercetin present in EAE attenuated the inflammation by down-regulating the CCl 4 -induced activation of nuclear factor-kappa B, tumor necrosis factor-α and cyclooxygenase and showed hepatoprotective effects. [51] …”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated the antioxidant potential of quercetin and lipoic acid against metal/ metalloid-induced oxidative stress in mice. [13][14][15] The present study was aimed at investigating the comparative protective efficacy of alpha-lipoic acid and quercetin against nanoparticle induced oxidative injury. Liver was selected as the major organ for investigation as it is the major target for free radical attack leading to lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%